x - x2 - 9x + 14 = 0 ; whence, x2 + 8x = 14 , x2 + 8x + 16 = 30 , and x + 4 = ±√30 . Therefore, x = ±√30 - 4 .
2y - 9x = 14 2y = 14 + 9x y = (14 + 9x) / 2
9x-6xy = 3
7x - 9x = -2x
-58.75 * 9x = -528.75x
9x = 100 - 30 + 11 9x = 81, x = 9
9 x 14 x 30 = 11340
(9x - 10)(x + 3)
3x2-9x-30 =3x2+6x-15x-30 =3x(x+2)-15(x+2) =(3x-15)(x+2) OR 3(x - 5)(x+2)
x - x2 - 9x + 14 = 0 ; whence, x2 + 8x = 14 , x2 + 8x + 16 = 30 , and x + 4 = ±√30 . Therefore, x = ±√30 - 4 .
9x is the lowest common multiple. (9x * 1 = 9x) (x * 9 = 9x)
(9x)2 +9x/(45x)2 +81= 9+9x/86
9x - 8 = 46 9x = 46 +8 9x= 54 9x/9 = 54/9 x= 6
9x+6=51 9x = 45 x= 5 9x-6=51 9x = 57 x= 6.33
9x+27 = -81 9x = -81-27 9x = -108 x = -12
2y - 9x = 14 2y = 14 + 9x y = (14 + 9x) / 2
-9x-25=3 -9x=28 9x=-28 x=-28/9